Local oxidation and reduction of graphene. (6th September 2017) - Hong, Yi-Zhe; Chiang, Wei-Huan; Tsai, Hung-Chieh; Chuang, Min-Chiang; Kuo, Yan-Chien; Chang, Lo-Yueh; Chen, Chia-Hao; White, Jonathon-David; Woon, Wei-Yen
Abstract: Micrometer sized oxidation patterns were created in chemical vapor deposition grown graphene through scanning probe lithography (SPL) and then subsequently reduced by irradiation using a focused x-ray beam. Throughout the process, the films were characterized by lateral force microscopy, micro-Raman and micro-x-ray photoelectron spectroscopy. Firstly, the density of grain boundaries was found to be crucial in determining the maximum possible oxygen coverage with SPL. Secondly, the dominant factor in SPL oxidation was found to be the bias voltage. At low voltages, only structural defects are formed on grain boundaries. Above a distinct threshold voltage, oxygen coverage increased rapidly, with the duration of applied voltage affecting the final oxygen coverage. Finally, we found that, independent of initial conditions, types of defects or the amount of SPL oxidation, the same set of coupled rate equations describes the reduction dynamics with the limiting reduction step being C–C → C=C.